Brevicidine acts as an effective sensitizer of outer membrane-impermeable conventional antibiotics for Acinetobacter baumannii treatment - Zhong, Xinyi; Deng, Kai; Yang, Xiuhan; Song, Xu; Zou, Yuanfeng; Zhou, Xun; Tang, Huaqiao; Li, Lixia; Fu, Yuping; Yin, Zhongqiong; Wan, Hongping; Zhao, Xinghong (Frontiers in Microbiology, 2023)
The antibiotic resistance of Acinetobacter baumannii poses a significant threat to global public health, especially those strains that are resistant to carbapenems. Therefore, novel strategies are desperately needed for the treatment of infections caused by antibiotic-resistant A. baumannii. In this study, we report that brevicidine, a bacterial non-ribosomally produced cyclic lipopeptide, shows synergistic effects with multiple outer membrane-impermeable conventional antibiotics against A. baumannii. In particular, brevicidine, at a concentration of 1 μM, lowered the minimum inhibitory concentration of erythromycin, azithromycin, and rifampicin against A. baumannii strains by 32–128-fold. Furthermore, mechanistic studies were performed by employing erythromycin as an example of an outer membrane-impermeable conventional antibiotic, which showed the best synergistic effects with brevicidine against the tested A. baumannii strains in the present study. The results demonstrate that brevicidine disrupted the outer membrane of A. baumannii at a concentration range of 0.125–4 μM in a dose-dependent manner. This capacity of brevicidine could help the tested outer membrane-impermeable antibiotics enter A. baumannii cells and thereafter exert their antimicrobial activity. In addition, the results show that brevicidine–erythromycin combination exerted strong A. baumannii killing capacity by the enhanced inhibition of adenosine triphosphate biosynthesis and accumulation of reactive oxygen species, which are the main mechanisms causing the death of bacteria. Interestingly, brevicidine and erythromycin combination showed good therapeutic effects on A. baumannii-induced mouse peritonitis–sepsis models. These findings demonstrate that brevicidine is a promising sensitizer candidate of outer membrane-impermeable conventional antibiotics for treating A. baumannii infections in the post-antibiotic age.